Streptococcus y su influencia en infecciones respiratorias en niños menores de 5 años, área de consulta externa pediátrica del Hospital IESS Milagro, octubre 2018-abril 2019 - Vera Villegas, Jenniffer Elizabeth (2019)
Respiratory infections are the leading cause of morbidity and mortality in children around the world, where the Streptococcus is the most frequent Etiologic Agent, most of these species can be found in the body without causing any type of disease but There may be an imbalance between the various species of micro-organisms that are found in the body, generating as a consequence the proliferation of this type of bacteria, causing many especially respiratory diseases. General objective: to determine the different types of Streptococcus that influence respiratory infections in children under 5 years in the area of Pediatric outpatient Hospital IESS Milagro. Methods used: deductive and analytic and synthetic, that are implemented is the quantitative and research types used were: non-experimental, descriptive and Transversal. Results: 70% the two types of most common Streptococcus are S. Pyogenes and S Pneumoniae. The risk factor most prevailing with a 41% is the dump of garbage around the houses and climate change. Mothers with a 81% have no knowledge about the complications that can arise if minors are not served on time, and 74% do not know the higienicas-alimentarias norms that are fundamental to a respiratory infection. Conclusion: the hypothesis is correct since different types of Streptococcus that are influencing the triggering of respiratory infections were determined and execute the proposal put forward for the benefit of children.